Flexible cantilever retaining walls: design according to Eurocode 7 and classical methods - Castorina Vieira (2002)
The paper presents a comparative study on the design of flexible cantilever retaining walls using classical limit equilibrium methods and a finite element model. The conventional approaches of introducing safety in the calculations are referred as well as the Cases B+C approach established in Eurocode 7. The results of the design, in particular the wall embedded height and the maximum bending moment, provided by the distinct approaches are discussed and compared. A discussion is presented on the way to deal with Cases B+C approach when finite element analyses instead of limit equilibrium methods are used. Considering a simple numerical case study, the results from a set of finite element simulations, considering cantilever walls designed by means of a classical and Cases B+C approaches, are discussed. Some practical conclusions are drawn.